Intercomparison of Monte Carlo calculated dose enhancement ratios for gold nanoparticles irradiated by X-rays: Assessing the uncertainty and correct methodology for extended beams. (April 2021) - Rabus, H.; Li, W.B.; Villagrasa, C.; Schuemann, J.; Hepperle, P.A.; de la Fuente Rosales, L.; Beuve, M.; Di Maria, S.; Klapproth, A.P.; Li, C.Y.; Poignant, F.; Rudek, B.; et al.
Highlights: Realistic dose enhancement of gold nanoparticles for X-rays with secondary particle equilibrium. Novel approach to estimate uncertainty of correction for lack of secondary particle equilibrium. Set of consistency checks allowed identifying and correcting normalization problems. Good agreement of dose enhancement ratios for extended field within uncertainty of correction. DERs deviate from unity only within the first few 100 nm and maximum values are below 20. Abstract: Results of a Monte Carlo code intercomparison exercise for simulations of the dose enhancement from a gold nanoparticle (GNP) irradiated by X-rays have been recently reported. To highlight potential differences between codes, the dose enhancement ratios (DERs) were shown for the narrow-beam geometry used in the simulations, which leads to values significantly higher than unity over distances in the order of several tens of micrometers from the GNP surface. As it has come to our attention that the figures in our paper have given rise to misinterpretation as showing 'the' DERs of GNPs under diagnostic X-ray irradiation, this article presents estimates of the DERs that would have been obtained with realistic radiation field extensions and presence of secondary particle equilibrium (SPE). These DER values are much smaller than those for a narrow-beam irradiation shown in our paper, and significant dose enhancement is only found within a few hundred nanometers around the GNP. The approach used to obtain these estimates required the development of a methodology to identify and, where possible, correct results from simulations whose implementation deviated from the initial exercise definition. Based on this methodology, literature on Monte Carlo simulated DERs has been critically assessed.